Образовательная и языковая политика Украины как фактор языковых конфликтов - Берегсасі Аніко; Черничко Степан; Beregszászi Anikó; Csernicskó István; Csernicsko Istvan; Aniko Beregszaszi (PoliPrint Kft., 2011)
Ukrajna de jure egynyelvű állam, ám de facto többnyelvű. A deklarált jogi állapot nem fedi a gyakorlatban megfigyelhető nyelvi helyzetet. A narancsos forradalom révén hatalomra jutott nemzeti politikai elit egyik legfőbb célkitűzése volt, hogy összhangba hozza a de jure és a de facto helyzetet. Ez a törekvés azonban szemben állt a nem ukrán nyelvű lakosság érdekeivel és törekvéseivel.

Abstract. De jure Ukraine is a monolingual state, however de facto it is multilingual. In the country several languages are spoken besides Ukrainian. In Ukraine the de jure and the de facto situations do not coincide with each other. The Ukrainian political elite (which came to power after the orange revolution) would like to solve this problem by making Ukraine a monolingual state. The linguistic and nationality policy of the state do not take care the linguistic rights of the non-Ukrainian population.

Резюме. Украина – de jure одноязычное государство, но de facto – многоязыковая страна. Политическая элита, которая пришла к власти после оранжевой революции 2004 года, была намерена решить эту проблему путём превращения Украины (и de jure, и de facto) в одноязычную страну. Государственная языковая и национальная политика при этом не обращала никакого внимания на языковые права не украиноязычных граждан страны.
https://www.kmf.uz.ua/hun114/letoltes/acta/acta2011_1.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/137286
Keywords: образовательная политика; языковая политика; язык; языковой конфликт; Украина